Chitosan-modified lipid nanodrug delivery system for the targeted and responsive treatment of ulcerative colitis. (15th February 2020) - Chen, Shao-qing; Song, Yan-qing; Wang, Cheng; Tao, Shan; Yu, Fang-ying; Lou, Hai-ya; Hu, Fu-qiang; Yuan, Hong
Graphical abstract: Highlights: Chitosan-modified lipid nanoparticles have esterase-responsive property in vitro . Chitosan-modified drug-loaded lipid nanoparticles have colon-targeting effects. Chitosan-modified lipid nanoparticles can protect the integrity of colon barrier. Chitosan-modified lipid nanoparticles exhibit superior anti-inflammatory effects. Abstract: Targeted and sensitive drug release at the colitis site is critical for the effective therapy of ulcerative colitis and reduction of side effects from the drug. Herein, we used 3, 3′-dithiodipropionic acid (DTPA) to covalently link quercetin (Qu) and glyceryl caprylate-caprate (Gcc) via ester bonds to prepare Qu-SS-Gcc lipid nanoparticles (Qu-SS-Gcc LNPs). Dexamethasone (Dex) was used as a model drug, and chitosan (CSO) was modified on the surface of Qu-SS-Gcc LNPs to obtain CSO-modified Dex-loaded Qu-SS-Gcc LNPs (CSO/Dex/LNPs). The encapsulation efficiency and drug loading of CSO/Dex/LNPs were 93.1 % and 8.1 %, respectively. The in vitro release results showed that CSO/Dex/LNPs had esterase-responsive characteristics and could release the drug rapidly in esterase-containing artificial intestinal fluid. A human colorectal adenocarcinoma cell (Caco-2) monolayer was used as the intestinal cell barrier model. Transmembrane resistance measurements and permeation experiments showed that CSO/Dex/LNPs had a protective effect on the lipopolysaccharide (LPS)-stimulated Caco-2 cell monolayer and increased the expression of E-cadherin in LPS-stimulated Caco-2 cells. Moreover, CSO/Dex/LNPs could significantly reduce the expression of the inflammatory factors TNF-α, IL-6 and NO in LPS-stimulated RAW 264.7 cells. The ulcerative colitis mouse model was constructed by using C57BL/6 mice. The in vivo distribution results showed that CSO/Dex/LNPs had colon-targeting effects and strong retention ability in the colons of mice with colitis. The results also showed that CSO/Dex/LNPs had better anti-inflammatory effects than free Dex, which could reduce colonic atrophy, reduce histomorphological changes and increase the expression of E-cadherin in the colon. Furthermore, the expression levels of TNF-α, IL-6 and NO in the CSO/Dex/LNP-treated group were 37.4 %, 35.5 % and 33.2 % of those in mice with colitis, respectively.